2018
DOI: 10.1002/ar.23914
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Development of the Atrial Septum

Abstract: The complete division of the atrial cavity by a septum, resulting in a left and right atrium, is found in many amphibians and all amniotes (reptiles, birds, and mammals). Surprisingly, it is only in eutherian, or placental, mammals that full atrial septation necessitates addition from a second septum. The high incidence of incomplete closure of the atrial septum in human, so‐called probe patency, suggests this manner of closure is inefficient. We review the evolution and development of the atrial septum to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 117 publications
(199 reference statements)
3
68
0
Order By: Relevance
“…The pronounced offset in birds may reflect in part that the membranous septum of the ventricle completely myocardialises (Adams, ). In crocodylians this septum only exhibits slight myocardialization (Jensen et al, ) and mammals always have the membranous septum present in the adult heart (Rowlatt, ). We confirm the constant presence of a large left atrioventricular junction guarded by membranous leaflets anchored to papillary muscles, a feature crocodylians and birds share with mammals (Jensen et al, ; Cook et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pronounced offset in birds may reflect in part that the membranous septum of the ventricle completely myocardialises (Adams, ). In crocodylians this septum only exhibits slight myocardialization (Jensen et al, ) and mammals always have the membranous septum present in the adult heart (Rowlatt, ). We confirm the constant presence of a large left atrioventricular junction guarded by membranous leaflets anchored to papillary muscles, a feature crocodylians and birds share with mammals (Jensen et al, ; Cook et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The atrial septum of monotreme and marsupial mammals develops from the primary septum only. In eutherian mammals, the atrial septum is formed by the merger of the primary and secondary atrial septum, a process that is revealed in the adult heart by the presence of the fossa ovale (Röse, ; Runciman, Gannon, & Baudinette, ; Jensen, Wang, & Moorman, ). In contrast, the atrial septum of birds has no fossa ovale and it develops from the primary septum only (Jensen, Wang, Moorman, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the human population, deficient PDGF signaling is related to pulmonary vein abnormalities . A major structure in atrium development found in many amphibians and in amniotes (reptiles, birds, mammals) is the atrium septum, dividing the common atrium into left‐ and right‐sided chambers. The primary foramen is closed collaboratively by the AV cushions, the mesenchymal cap, and the DMP, tissues that can also be found in lungfish .…”
Section: The Atrial Segmentmentioning
confidence: 99%
“…A major structure in atrium development found in many amphibians and in amniotes (reptiles, birds, mammals) is the atrium septum, dividing the common atrium into left‐ and right‐sided chambers. The primary foramen is closed collaboratively by the AV cushions, the mesenchymal cap, and the DMP, tissues that can also be found in lungfish . In placental mammals, septation is completed by addition of the second septum, while definitive closure of the septum is completed only after birth.…”
Section: The Atrial Segmentmentioning
confidence: 99%
See 1 more Smart Citation